Accelerated weathering and decay resistance of heat-treated wood reinforced polypropylene composites : Ubrzano izlaganje polipropilenskih kompozita ojačanih pregrijanim drvom vremenskim utjecajima i otpornost na propadanje - Aydemir, Deniz (Array, 2019)
The aim of this study was to determine the accelerated weathering and decay resistance of the heattreated wood reinforced polypropylene composites (HT-WPC). Polypropylene (PP) was used as a matrix and the heat-treated wood treated at 180 °C and 220 °C as reinforcement filler. The effect of three filler type, such as 40, 60 and 100 mesh, on the outdoor performance of composites was also investigated. The composites were prepared with twin screw extruder, and the test samples were obtained with compression molding. Lightness index (L*), color changes (ΔE*) and physical changes on the surface of the composites after the accelerated weathering, and decay resistance of the composites were investigated. According to the results, the effects of heat-treated wood on color changes were found to be more than its filler size, and while the filler loadings were increased from 5 % to 20 %, it was determined to increase the color changes of the composites. In scanning electron microscopy (SEM) images, crack formation and deterioration on the surface of the composites were determined. In FTIR spectra, no difference was determined between the composites, and all peaks were similar to each one. The addition of heattreated wood improved the antifungal efficiency of the composite, and the mass losses decreased with the increasing of heat treatment temperature. As a result, adding heat-treated wood to PP was found to improve the outdoor performance of the HT-WPCs.